2012
DOI: 10.1111/j.1539-6924.2012.01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation as an Approach to Understanding Hurricane Risk Response: Insights from the Stormview Lab

Abstract: This article investigates the use of dynamic laboratory simulations as a tool for studying decisions to prepare for hurricane threats. A prototype web-based simulation named Stormview is described that allows individuals to experience the approach of a hurricane in a computer-based environment. In Stormview participants can gather storm information through various media, hear the opinions of neighbors, and indicate intentions to take protective action. We illustrate how the ability to exert experimental contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 29 publications
6
42
0
Order By: Relevance
“…Earthquake experience has been linked to increased risk perception for future earthquakes and greater preparation for them [46]. But having previously experienced a hurricane has been linked to lower levels of concern about future hurricanes and less preparedness [47]. A meta-analysis of 21 actual hurricane evacuation studies and two hypothetical ones found no correlation between previous hurricane experience and evacuation [25].…”
Section: Prior Storm Experiencementioning
confidence: 99%
“…Earthquake experience has been linked to increased risk perception for future earthquakes and greater preparation for them [46]. But having previously experienced a hurricane has been linked to lower levels of concern about future hurricanes and less preparedness [47]. A meta-analysis of 21 actual hurricane evacuation studies and two hypothetical ones found no correlation between previous hurricane experience and evacuation [25].…”
Section: Prior Storm Experiencementioning
confidence: 99%
“…Risk perceptions are often used to examine how people recognize and identify risk; they include understanding the probability of a risk happening at a particular place during a particular time and the probability of consequences from this risk (Meyer, Broad, Orlove & Petrovic, ; Mileti et al., ; Wu et al., , Zhu et al., ). The perception of the risk is usually considered a central factor influencing the reaction of people towards it in PADM (Lindell et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rather, communication strategies need to tap into the affective and analytical aspects of human decision making by presenting climate change in a form that people can relate to on the timescales they care about and at relevant spatial scales (O'neill & Nicholson‐Cole, ). This includes reframing the problem in terms of contemporary, local impacts and diverse ideological norms, employing narratives in lieu of statistical descriptions for public consumption, and utilizing advances in computer technology and access to let people play simulation games where their futures can be made explicit (Meyer, Broad, Orlove, & Petrovic, ). Yet even when people are aware of climate change and have experienced impacts first hand, there is often a tendancy to avoid thinking about it or console oneself with apparent claims to virtue such as “there are worse polluters” (Norgaard, ).…”
Section: Discussionmentioning
confidence: 99%